2005
DOI: 10.1051/rnd:2005005
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein restriction during lactation in primiparous sows with different live weights at farrowing: II. Consequences on reproductive performance and interactions with metabolic status

Abstract: -The hypothesis that the restriction of dietary protein during lactation has different impacts on reproductive performance in light and heavy sows at farrowing was investigated, as well as the relationships between reproductive parameters and sow metabolic data. At farrowing, 38 primiparous sows were assigned to one of three groups: sows weighing 180 kg not restricted in dietary protein during lactation (180CP); sows weighing 180 or 240 kg restricted in protein (180LP and 240LP). Twenty-four sows were catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
1
9
0
3
Order By: Relevance
“…The greater the reserves are at farrowing, the higher they will be at weaning (Whittemore, 1996;Young et al, 2004;Clowes, 2006), which was confirmed in this study. The relationship observed between BW and BT at farrowing with greater losses during lactation confirms that the largest mobilization of reserves occurs in females that are heavier (Quesnel et al, 2005b) or fatter (Young et al, 2004) at parturition. This can be explained by the reduced feed intake in fat sows (Revell et al, 1998a;Young et al, 2004;Quesnel et al, 2005a), mainly during the first two weeks of lactation, which can be related to the circulating concentration or oxidation of NEFA and glycerol (Revell et al, 1998a) or to an insulin resistance state in heavy sows (Quesnel et al, 2005a).…”
Section: Bwf Classessupporting
confidence: 57%
See 2 more Smart Citations
“…The greater the reserves are at farrowing, the higher they will be at weaning (Whittemore, 1996;Young et al, 2004;Clowes, 2006), which was confirmed in this study. The relationship observed between BW and BT at farrowing with greater losses during lactation confirms that the largest mobilization of reserves occurs in females that are heavier (Quesnel et al, 2005b) or fatter (Young et al, 2004) at parturition. This can be explained by the reduced feed intake in fat sows (Revell et al, 1998a;Young et al, 2004;Quesnel et al, 2005a), mainly during the first two weeks of lactation, which can be related to the circulating concentration or oxidation of NEFA and glycerol (Revell et al, 1998a) or to an insulin resistance state in heavy sows (Quesnel et al, 2005a).…”
Section: Bwf Classessupporting
confidence: 57%
“…Body reserves at farrowing may be protective against a reduction of feed intake during lactation (Clowes, 2006). Milk output (Revell et al, 1998b), ovarian function (Clowes et al, 2003b) and return to reproductive activity after weaning (Mullan and Williams, 1989;Quesnel et al, 2005b) can be affected by body condition at farrowing. In the present study, absolute body reserves at farrowing and at weaning were shown to be important for the increase of SLS, emphasizing that performance of primiparous sows is affected by the mobilization of body reserves, but the response is also determined by the amount of reserves present at the beginning of lactation (Mullan and Williams, 1989).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…The sows were slaughtered 30 ± 1 d after insemination for examination of the genital tracts. This part is extensively described in a companion paper [14].…”
Section: Dietsmentioning
confidence: 99%
“…For example, in hot climate, reducing the total protein content of the diet will minimize heat production and favour appetite (Silva et al, 2009). Third, increasing sow body reserves at farrowing has been shown to reduce the impact of protein deficiency during lactation (Clowes et al, 2003;Quesnel et al, 2005). Moreover, as mentioned above, restricting feeding during pregnancy may be associated with hunger and behavioural disorders.…”
Section: Reproductive Sows and Suckling Pigletsmentioning
confidence: 99%